Exposure of Physalaemus cuvieri (Anura) to benzo[a]pyrene and α-naphthoflavone: Morphofunctional effects on hepatic melanomacrophages and erythrocytes abnormalities - Fanali, Lara Zácari [UNESP]; Sturve, Joachim; de Oliveira, Classius [UNESP] (Elsevier, 2021)
Benzo[a]pyrene (BaP) is a high-risk contaminant of elevated toxicity. Its biotransformation process occurs as the expression of CYP1A1 increases and produces toxic metabolites. In turn, α-naphthoflavone (aNF) represents an inhibitor of CYP1A1, preventing BaP metabolism. Toxicological studies in anurans show alterations in the melanomacrophage (MM) detoxification cell after exposure to xenobiotics. In this study, the production of melanin by MMs was evaluated, as were morphological alterations in the cytoskeleton, phagocytosis and the genotoxicity effects after exposure of an anuran species to BaP and aNF. Physalaemus cuvieri received subcutaneous injections of 2 mg/kg and/or 20 mg/kg aNF. For phagocytosis analyses, animals received an intraperitoneal injection with 0.4% trypan blue. The results revealed that melanin synthesis increased by 503.2% in animals exposed to BaP after 48 h, which was related to the antioxidant action of melanin, whereas the decreased in synthesis of 25.6% with the BaP + aNF interaction resulted in high toxicity to MMs and cell degeneration. The phagocytic activity reduced to 37.6% in animals exposed to BaP, characterizing a functional impairment; however, the BaP + aNF interaction led to the restoration of phagocytosis, reaching 419.23%. The decreased rate or absence of abnormalities may be explained by the fact that only the less damaged erythrocytes remained in the bloodstream, whereas the most damaged cells died. In conclusion, BaP and aNF are toxic to P. cuvieri, bringing risks to herpetofauna.
Keywords: Detoxification; Liver; Melanin; Microtubules